2001
DOI: 10.1046/j.1365-2427.2001.00652.x
|View full text |Cite
|
Sign up to set email alerts
|

Chironomid stratigraphy in the shallow and eutrophic Lake Søbygaard, Denmark: chironomid–macrophyte co‐occurrence

Abstract: 1. A sediment core from the shallow, hypertrophic Lake Søbygaard (mean depth ∼1 m; [TP] 310 μg P L−1) was analysed for subfossil remains to reconstruct chironomid community changes in relation to the succession and disappearance of aquatic macrophytes. 
2. Species composition in the 1.10 m core indicates a succession from a ‘naturally’ eutrophic state to a hypertrophic state during recent centuries. Radiometric dating (210Pb) of the uppermost 20 cm of the sediment core (∼1932–93) indicates that sediment accumu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
143
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(156 citation statements)
references
References 60 publications
10
143
0
3
Order By: Relevance
“…5b) which suggests a strong secondary control on the assemblage that co-varies with eutrophication. In a palaeo-study of chironomid-macrophyte relationships from shallow, eutrophic Lake Søbygaard, Denmark (Brodersen et al 2001), changing macrophyte assemblage structure was identified as a key likely driver of chironomid community changes. Given the range of lake microhabitats occupied by testate amoebae (Lansac-Tôha et al 2014) and the synchronous response of both groups demonstrated here, it seems likely that similar relationships may also exist between testate amoebae and aquatic macrophytes.…”
Section: Mechanisms Of Changementioning
confidence: 99%
“…5b) which suggests a strong secondary control on the assemblage that co-varies with eutrophication. In a palaeo-study of chironomid-macrophyte relationships from shallow, eutrophic Lake Søbygaard, Denmark (Brodersen et al 2001), changing macrophyte assemblage structure was identified as a key likely driver of chironomid community changes. Given the range of lake microhabitats occupied by testate amoebae (Lansac-Tôha et al 2014) and the synchronous response of both groups demonstrated here, it seems likely that similar relationships may also exist between testate amoebae and aquatic macrophytes.…”
Section: Mechanisms Of Changementioning
confidence: 99%
“…Conversely, of the eight taxa of Orthocladiinae found as subfossils, only Nanocladius and three taxa in the genus Cricotopus were found as living larvae (Table 2). However, the number of living invertebrates found at each sampling station was high (49-1,173, with the exception of 23 specimens at 4.5 m water depth), and the number of identified chironomid head capsules (36-72) from subfossil Several genera that were encountered only in subfossil assemblages such as Corynoneura, Dicrotendipes, Endochironomus, and Metriocnemus are often associated with macrophytes (Pinder and Reiss 1983;Brodin 1986;Brodersen et al 2001;Merritt et al 2008;Moller Pillot 2009). Other groups, such as Bryozoa, are associated with woody substrates or aquatic macrophytes (Wood and Okamura 2005) and Xenochironomus xenolabis is known to be a parasite on Spongillidae (Pinder and Reiss 1983;Moog 2002).…”
Section: Occurrence Of Taxa In Lake De Waaymentioning
confidence: 99%
“…Interest in plant macrofossils is greatly increasing, not only to provide terrestrial material for 14 C AMS dating, but also to help understand changes in aquatic biota in multi-proxy studies (e.g. Sayer et al 1999Sayer et al , 2006Birks et al 2001;Brodersen et al 2001;Odgaard and Rasmussen 2001;Bradshaw et al 2005b;Davidson et al 2005).…”
Section: Pollen Analysis and Plant Macrofossilsmentioning
confidence: 99%